Startups, Unicorns, and the Local Influx of Inventors - Balsmeier, Benjamin; Fleming, Lee; Marx, Matt; Shin, Seungryul Ryan (The Review of Economics and Statistics, 2025)
We provide evidence that an influx of technical human capital improves regional entrepreneurship, both by increasing firm entry and reducing entrepreneurial failure. The results also indicate negative externalities upon lowtech and competing industries: an influx of inventors in a county shifts the locus of venture capital investment away from low-tech startups to high-tech startups and moreover towards new ventures in the same sector as those inventors' skills. We strengthen causal inference with a shift-share instrument which combines the spatial distribution of surnames in the LM>= U.S. Census with thousands of surnamespecific shifts based on modern inventor mobility.